2020
DOI: 10.1186/s40359-020-00428-y
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in primary school children as a route to enhanced life satisfaction, positive outlook and effective emotion regulation

Abstract: Background Mindfulness programmes as a potential avenue of enhancing pupil wellbeing are beginning to show great promise. However, research concerning the effectiveness of mindfulness training for primary aged school children (7–11 years of age) has been neglected. Methods Building on methodological limitations of prior research, this study employed an active controlled design to assess the longer term wellbeing and emotion regulation outcomes after a 6 week mindfulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 58 publications
1
18
0
2
Order By: Relevance
“…Mindfulness is defined as the attention and awareness of the current experiences, characterized by non-critical observation and experience of current experience ( Brown and Ryan, 2003 ; Brown et al, 2007 ). Generally speaking, the present studies can be divided into experimental and observational methods: for one thing, mindfulness based on intervention had a noteworthy impact on life satisfaction ( Harnett et al, 2010 ; Henriksson et al, 2016 ; Lötzke et al, 2016 ; Chandrasekara, 2018 ; Amundsen et al, 2020 ; Gupta and Verma, 2020 ); for another thing, individuals with trait mindfulness tended to have higher scores of life satisfaction. Moreover, existing research has preliminarily expanded the path between mindfulness and life satisfaction.…”
Section: Introductionmentioning
confidence: 94%
“…Mindfulness is defined as the attention and awareness of the current experiences, characterized by non-critical observation and experience of current experience ( Brown and Ryan, 2003 ; Brown et al, 2007 ). Generally speaking, the present studies can be divided into experimental and observational methods: for one thing, mindfulness based on intervention had a noteworthy impact on life satisfaction ( Harnett et al, 2010 ; Henriksson et al, 2016 ; Lötzke et al, 2016 ; Chandrasekara, 2018 ; Amundsen et al, 2020 ; Gupta and Verma, 2020 ); for another thing, individuals with trait mindfulness tended to have higher scores of life satisfaction. Moreover, existing research has preliminarily expanded the path between mindfulness and life satisfaction.…”
Section: Introductionmentioning
confidence: 94%
“…At the same time, researchers should further develop effective strategies (e.g., mindfulness), starting with individual emotional training, so that individuals can master emotional types, understand emotional characteristics, and alleviate the negative effects of alexithymia on SA by enhancing their ability to identify and describe emotions ( Gao T. et al, 2018 ; Li and Hao, 2019 ). In addition, most studies have shown that mindfulness can significantly improve subjective well-being and life satisfaction, enhance positive emotions, and reduce negative emotions ( Shapiro et al, 2007 ; Kieviet-Stijnen et al, 2008 ; Amundsen et al, 2020 ). In addition, researchers can use psychological counseling and treatment programs such as group therapy ( Yuchang et al, 2017 ) to focus on attachment construction and help smartphone addicts establish healthy attachment relationships and secure attachment styles.…”
Section: Discussionmentioning
confidence: 99%
“…However, four programs reported non-significant effects of SEL on student mental health outcomes [ 44 47 ], while two programs demonstrated increased levels of anxiety [ 48 ] and a reduction of subjective well-being [ 49 ] at post-intervention. Mindfulness-based curriculum showed its potential to endorse positive outcomes for youth including reduced emotional problems and negative affect [ 50 56 ] as well as increased well-being and positive emotions [ 51 , 52 , 57 60 ], especially among high-risk children with emotional problems or perceived stress before interventions [ 50 , 53 ]. However, non-significant effects were also reported in an Australian study in secondary schools [ 61 ].…”
Section: Resultsmentioning
confidence: 99%